Up-to-date methods of stomach functions investigation and their diagnostic potentials - Ya. S. Tsimmerman (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate features of application of up-to-date methods of evaluation of various functions of the stomach in clinical practice.Original positions. In the review qualities and faults of tube aspiration method of stomach secretory function investigation at continuous (complete) extraction of gastric juice are discussed as well as advantages of various methods of intragastric pH-metry. Advantages of modern multichannel рН-meters, potential of acquiring of the supplemental information by original methods of intragastric рН-grams analysis with application of various pharmacological and stimulaion tests are analyzed. Methods of studying of gastric juice proteolytic activity are compared. Diagnostic descriptive value of methods of electrogastrography and methods of mathematical analysis of electrogastrograms developed by the author, and potential of radionuclide methods are reviewed. Advantages of transillumination functional hemomotordynamic monitoring of the stomach and intragastric impedance measurement at studying functions of the stomach are shown.Conclusion. The up-to-date methods of investigation used in clinical practice, allow to receive complete information on functional state of the stomach.